2010
DOI: 10.1148/radiol.10100200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Features of Pancreatobiliary- and Intestinal-type Ampullary Carcinomas at MR Imaging

Abstract: Purpose:To defi ne the differential imaging features of pancreatobiliaryand intestinal-type ampullary carcinomas at magnetic resonance (MR) imaging and to correlate these features with pathologic fi ndings. Materials and Methods:This retrospective study was approved by the institutional review board; informed consent was waived. Fifty patients with surgically confi rmed ampullary carcinoma and preoperative MR results were included. Two radiologists, blinded to histologic type of cancer, evaluated imaging fi nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 27 publications
1
18
1
1
Order By: Relevance
“…Chung et al revealed that an oval filling defect at the distal end of the bile duct on MRCP images is likely to suggest an intestinal‐type ampullary carcinoma. Our results were different from their study, since none of the MRCP image features of the tumors in our study were significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chung et al revealed that an oval filling defect at the distal end of the bile duct on MRCP images is likely to suggest an intestinal‐type ampullary carcinoma. Our results were different from their study, since none of the MRCP image features of the tumors in our study were significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…When ROC curve analysis was performed with combined model of enhancement pattern and ADC min value, the area under the curve increased to 0.807, with the sensitivity and specificity being 70.4% and 78.6%, respectively. Chung et al 26 revealed that an oval filling defect at the distal end of the bile duct on MRCP images is likely to suggest an intestinal-type ampullary carcinoma. Our results were different from their study, since none of the MRCP image features of the tumors in our study were significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated the significance of a filling defect detected on MRCP and have suggested that a filling defect could be a sign of bile duct carcinoma or papillomatosis [18][19][20] . In addition, intra-ductal debris, sludge, and stones could be causes of a filling defect after LT [21] .…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study found that the comprehensive evaluation of multiple CT features of the periampullary area could differentiate the histological subtypes, but required optimal duodenal distention and was highly dependent on the expertise of the radiologists[15]. An oval filling defect at the end of the bile duct on magnetic resonance cholangiopancreatography images tended to suggest IPAC but controversy still existed[16,17].…”
Section: Introductionmentioning
confidence: 99%